Failure to Attain HIV Viral Suppression After Intensified Adherence Counselling—What Can We Learn About Its Factors? - Mundamshimu JS; Malale K; Kidenya BR; Gunda DW; Bwemelo L; Mwashiuya M; Omar SS; Mlowe N; Kiyumbi M; Ngocho JS; Balandya E; Sunguya B; et al. (Infection and Drug Resistance, 2023)
James Samwel Mundamshimu,1 Kija Malale,1 Benson R Kidenya,1 Daniel W Gunda,1 Logious Bwemelo,1,* Mwakile Mwashiuya,1,* Salhida Shamnte Omar,1,* Neema Mlowe,1,* Magwa Kiyumbi,1 James S Ngocho,2,3 Emmanuel Balandya,4 Bruno Sunguya,4 Stephen E Mshana,1 Kien Mteta,2 John Bartlett,5,6 Eligius Lyamuya,4 Blandina Theophil Mmbaga,2,3 Samuel Kalluvya1 1Catholic University of Health and Allied Sciences, Mwanza, Tanzania; 2Kilimanjaro Christian Medical University College, Moshi, Tanzania; 3Kilimanjaro Clinical Research Institute, Moshi, Tanzania; 4Muhimbili University of Health and Allied Sciences, Dar es Salaam, Tanzania; 5Kilimanjaro Christian Medical University College, Mosh, Tanzania; 6Duke Global Health Institute, Duke University Medical Center, Durham, NC, USA*These authors contributed equally to this workCorrespondence: James Samwel Mundamshimu, Tel +255746999249, Email jamessamwel913@yahoo.comBackground: Introduction and expansion of antiretroviral therapy (ART) have turned the tide of HIV pandemic, thus helping people living with HIV (PLHIV) achieve viral suppression. This success may need to be complemented by intensified adherence counseling (IAC) to improve adherence to treatment. However, some PLHIV still face higher than acceptable viral loads despite being on treatment.Purpose: We investigated the factors associated with the failure to suppress HIV viral load after three months of IAC sessions.Patients and Methods: This cross-sectional study analyzed secondary data from PLHIV-attended care and treatment clinics in Mwanza between January 2018 and December 2019 who had unsuppressed VL after being on ART for at least six months. We identified PLHIV in first-line ART with viral load evaluation before receiving IAC and had viral load results done at 90 days after IAC. We conducted descriptive statistics to examine the magnitude of viral suppression. Wilcoxon signed-rank test used to compare the median viral load before and after IAC sessions, and logistic regressions predicted the factors associated with failure.Results: This study included 212 subjects. After intervention, most participants 85.9% (182) had significantly improved adherence compared to baseline. More than half 75.5% (160) of the participants had viral suppression after the intervention. Participants aged 18– 25 years (AOR = 5.6, 95% CI, 1.1– 29.6), unstable client during ART initiation (AOR = 0.3, 95% CI, 0.13– 0.62), and poor adherence to ART (AOR = 4, 95% CI, 1.3– 12.3) remained the main predictors of virological failure after IAC intervention.Conclusion: Even though virological suppression is influenced by ART adherence, the findings in this study have shown co-existence of other factors to be addressed. Unstable during ART initiation is a new factor identified in this study.Keywords: people living with HIV, virological failure, intensified adherence counseling, factors, Tanzania